2008
DOI: 10.1118/1.2989019
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of neutron ambient dose equivalent in passive carbon‐ion and proton radiotherapies

Abstract: Secondary neutron ambient dose equivalents per the treatment absorbed dose in passive carbon-ion and proton radiotherapies were measured using a rem meter, WENDI-II at two carbon-ion radiotherapy facilities and four proton radiotherapy facilities in Japan. Our measured results showed that (1) neutron ambient dose equivalent in carbon-ion radiotherapy is lower than that in proton radiotherapy, and (2) the difference to the measured neutron ambient dose equivalents among the facilities is within a factor of 3 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 25 publications
3
72
2
Order By: Relevance
“…Both experimental methods and Monte Carlo (MC) simulations were used in these studies Zacharatou Jarlskog et al, 2008;Jiang et al, 2005;Polf et al, 2005;Agosteo et al, 1998). For ions heavier than protons, measurements of neutron contamination in therapeutic ion beams are scarce and dedicated mainly to 12 C ion beams (Iwase et al, 2007;Gunzert-Marx et al, 2008;Yonai et al, 2008). Using MC calculations, different types of secondary radiation have been evaluated for a variety of ion beams (Porta et al, 2008;Iwase et al, 2007;Gunzert-Marx et al, 2008;Pshenichnov et al, 2005;Gudowska et al, 2007;Hultqvist and Gudowska, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Both experimental methods and Monte Carlo (MC) simulations were used in these studies Zacharatou Jarlskog et al, 2008;Jiang et al, 2005;Polf et al, 2005;Agosteo et al, 1998). For ions heavier than protons, measurements of neutron contamination in therapeutic ion beams are scarce and dedicated mainly to 12 C ion beams (Iwase et al, 2007;Gunzert-Marx et al, 2008;Yonai et al, 2008). Using MC calculations, different types of secondary radiation have been evaluated for a variety of ion beams (Porta et al, 2008;Iwase et al, 2007;Gunzert-Marx et al, 2008;Pshenichnov et al, 2005;Gudowska et al, 2007;Hultqvist and Gudowska, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…2͑a͒ at 20 cm from the field edge. Yonai et al, 37 using a WENDI-II detector, showed that the ambient dose equivalent among different facilities differs by up to a factor of 3. Their results for the dose equivalent at 50 cm from the isocenter are larger than Fig.…”
Section: Ivc Equivalent Dosementioning
confidence: 99%
“…1,[9][10][11][12][13][14] There are a few reports of neutron doseequivalent measurements made in proton therapy centers with either the wide-energy neutron detection instrument (WENDI) or smart WENDI (SWENDI), a type of Rem-meter that is sensitive over an energy range adequate for measuring neutrons from proton therapy. [14][15][16][17] Like standard Remmeters, however, these detectors provide only a single doseequivalent value and do not provide the neutron spectrum. There are also several reports of measurements with detectors such as track etch detectors 14,18 or thermoluminescent detectors 19 that have limited or no response to neutrons with energies greater than 10 MeV.…”
Section: Introductionmentioning
confidence: 99%